Developing student worksheets (LKPD) based on Problem-Based Learning (PBL) to improve students' learning outcomes - Nurhabibah Meha; Dian Armanto; Adi Sutopo (Himpunan Pengembang Kurikulum Indonesia, 2025)
Teaching materials are one of the important factors that influence the effectiveness of the learning process. This study aims to develop student worksheets (Lembar Kerja Peserta Didik or LKPD) based on Problem-Based Learning (PBL) that are feasible, practical, and effective. The study was conducted at SDN 105278 Tandam Hilir II. The study subjects were 22 4th-grade students. The research method employed was development research, utilizing the ADDIE development model. The research instruments were observation, interviews, questionnaires, and tests. The study's results showed that, according to the validator's validity test, the percentage of feasibility among material experts, language experts, and design experts was considered very valid. The results of the small group trial produced a percentage of very criteria. The percentage of practicality in the field test results was included as a key criterion for evaluation. Effectiveness was achieved at the field trial stage, with 22 students passing the post-test, ensuring that the gain score met the criteria for moderate effectiveness. Based on empirical observations that showed an increase in learning outcomes. This means that Student Worksheets based on PBL learning are effectively utilized in the mathematics learning process, resulting in a positive impact on student learning outcomes in grade IV of SDN 105278 Tandam Hilir II. Abstrak Bahan ajar merupakan salah satu faktor penting yang mempengaruhi efektivitas proses pembelajaran. Penelitian ini bertujuan untuk menghasilkan Lembar Kerja Peserta Didik berbasis pembelajaran Problem Based Learning (PBL) yang layak, praktis dan efektif. Penelitian dilaksanakan di SDN 105278 Tandam Hilir II. Subjek penelitian kelas IV berjumlah 22 orang peserta didik. Metode penelitian adalah penelitian pengembangan dengan model pengembangan ADDIE. Adapun Instrumen penelitian yaitu observasi, wawancara, angket dan tes. Hasil penelitian menunjukkan dari hasil uji validitas oleh validator persentase kelayakan ahli materi, ahli bahasa, dan ahli desain dinilai sangat valid. Hasil uji coba kelompok kecil menghasilkan persentase kriteria sangat. Persentase kepraktisan hasil uji lapangan termasuk ke dalam kriteria sangat praktis. Efektivitas dicapai pada tahap uji coba lapangan dengan 22 peserta didik (100 persen) lulus post-test sehingga skor gain memenuhi kriteria efektivitas sedang. Berdasarkan observasi empiris yang menunjukkan adanya peningkatan hasil belajar. Artinya Lembar Kerja Peserta Didik berbasis pembelajaran PBL efektif digunakan dalam proses pembelajaran matematika sehingga berdampak pada hasil belajar peserta didik di kelas IV SDN 105278 Tandam Hilir II. Kata Kunci: hasil belajar; lembar kerja peserta didik; LKPD; model PBL; pembelajaran berbasis masalah